Effects of pre‐slaughter stressor and feeding preventative Chinese medicinal herbs on glycolysis and oxidative stability in pigs. (26th October 2015) - Bai, Xiumei; Yan, Xue; Xie, Linqi; Hu, Xiaodong; Lin, Xi; Wu, Changzheng; Zhou, Ningcong; Wang, Anru; See, Miles Todd
Abstract: A total of 64 5‐month‐old Pietrain pigs were randomly allocated to four treatments with four replicates per treatment according to body weight. The pigs were fed either a standard corn‐soybean meal based control diet (treatments 1 and 2), the standard diet with 1% Lycium barbarum (LB) (treatment 3), or the standard diet with 1% Polygala tenuifolia Willd (PT) (treatment 4). Serum lactic acid and glucose concentrations were increased in stressed pigs ( P < 0.05). Addition of the herbs in the diet had no effect on the serum lactic acid concentration, but 1% LB decreased ( P < 0.05) serum glucose concentration in the stressed pigs. Pre‐slaughter stress also decreased ( P < 0.01) liver glycogen concentration and the decrease could be inhibited by addition of 1% LB in the diet ( P > 0.05). Pre‐slaughter stress increased the concentration of maleic dialdehyde (MDA) ( P < 0.05) and decreased glutathione peroxidase (GSH‐Px) activity in serum, while dietary 1% LB increased ( P < 0.05) the activity of GSH‐Px and decreased the concentration of MDA in the serum. In conclusion, pre‐slaughter stress induces oxidative stress in pigs and dietary supplementation with 1% LB improves antioxidant capacity in stressed pigs before slaughtering.